Gathering blue - Lowry, Lois (Graphia, 2000)
Lame and suddenly orphaned, Kira is mysteriously removed from her squalid village to live in the palatial Council Edifice, where she is expected to use her gifts as a weaver to do the bidding of the all-powerful Guardians.